ANALISIS PRODUKSI DAN POTENSI UNSUR HARA SERASAH MANGROVE DI CAGAR ALAM PULAU DUA SERANG, BANTEN - Indria Wahyuni (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2016)
The research has been conducted at mangrove forest of Pulau Dua conservation in Serang town of Banten province from September to November 2011. The purposes of study were to know the production and potential nutrient of mangrove litter and to expect the nutrients released into marine environment. The sample was taken by employing transect-square method. Mangrove litter avalanches were caught by litter-trap and the size was examined by filtering the litter in water flow which connected mangrove forest and marine. The potential nutrient production of mangrove litter was analyzed by administering nutrient analysis of C, N, and P in laboratory. The findings showed that the dominating mangrove types were Avicennia marina and Rhizophora apiculata with 51,43% and 36,19%.of relative density. The mangrove forest of Pulau Dua conservation produced 4,05 gr/m2 /day litters on average total or 14,78 ton/ha/year litters ; and the largest contributor was leaves. The production of litters’ potential nutrient achieved 0,3456 gr-C/m2/day or 1,2616 ton-C/ha/year, 0,0091 gr-N/m2/day or 0,0333 ton-N/ha/year, 0,0008 gr-P/m2/day or 0,0031 ton-P/ha/year. Mangrove forest of Pulau Dua conservation also contributed 855,4724 gr.day/m3 litters to marine waters.